2020
DOI: 10.1167/tvst.9.9.25
|View full text |Cite
|
Sign up to set email alerts
|

Training-Induced Changes in Radial–Tangential Anisotropy of Visual Crowding

Abstract: One of the diagnostic features of visual crowding, radial-tangential anisotropy, has been observed both in behavioral experiments as well as in responses of the blood-oxygenation-level-dependent (BOLD) functional magnetic resonance imaging (fMRI) signal. As has been shown previously, crowding is stronger for radially arranged flankers, and this tendency is reflected in BOLD signal suppression. In the current study, we examined the effect of practice on the neural correlates of crowding. We expected that traini… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
7
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 73 publications
0
7
0
Order By: Relevance
“…To estimate the reliability of our measurements we acquired each threshold twice. Previous work showed improved performance in crowding tasks for repeated measurements (Chung, 2007; Malania et al, 2020). From their figures we estimate the second-block benefit to be 13% for Malania et al and 20% for Chung.…”
Section: Discussionmentioning
confidence: 96%
“…To estimate the reliability of our measurements we acquired each threshold twice. Previous work showed improved performance in crowding tasks for repeated measurements (Chung, 2007; Malania et al, 2020). From their figures we estimate the second-block benefit to be 13% for Malania et al and 20% for Chung.…”
Section: Discussionmentioning
confidence: 96%
“…However, no study, to our knowledge, has tested the effect of attention manipulation on the spatial extent of radial crowding. Moreover, although one study demonstrated reduction of the radial–tangential anisotropy by learning ( Malania, Pawellek, Plank, & Greenlee, 2020 ), no study has investigated whether and how spatial attention reduces the radial–tangential anisotropy of crowding.…”
Section: Introductionmentioning
confidence: 99%
“…Fifth, we reproduced the previous finding that the mutual crowding of the squares increases with the number of flanking squares ( Manassi et al, 2013 ). In addition, we found a radial-tangential anisotropy ( Chung, 2013 ; Greenwood et al, 2017 ; Kwon et al, 2014 ; Malania et al, 2020 ; Toet & Levi, 1992 ). The target square in the horizontally aligned squares was more crowded than in the vertically aligned squares ( Figure 5 & Supplementary Figure S1 ).…”
Section: Discussionmentioning
confidence: 65%
“…Crowding has specific characteristics. For example, flankers in the radial orientation interfere stronger than flankers in the tangential orientation (radial-tangential anisotropy; Chung, 2013 ; Greenwood, Szinte, Sayim, & Cavanagh, 2017 ; Kwon, Bao, Millin, & Tjan, 2014 ; Malania, Pawellek, Plank, & Greenlee, 2020 ; Toet & Levi, 1992 ), which was explained by elliptic receptive fields in early visual areas ( Hubel, Wiesel, & Stryker, 1978 ; Silson, Reynolds, Kravitz, & Baker, 2018 ; Toet & Levi, 1992 ) or by an uneven sampling density in the early visual cortex ( Kwon & Liu, 2019 ; Motter & Simoni, 2007 ).…”
Section: Introductionmentioning
confidence: 99%